The effects of ignoring level shifts on systems cointegration tests - Carsten Trenkler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
In this paper I analyse the effects of ignoring level shifts in the data generating process (DGP) on systems cointegration tests that do not accommodate level shifts. I consider two groups of Likelihood Ratio tests based on procedures suggested by Johansen (1988, 1995) and Saikkonen & Lütkepohl (2000b). The Monte Carlo analysis reveals that ignoring level shifts reduces the tests' sizes to zero and causes an important drop in the small sample power for increasing shift magnitudes. These observations are also reflected in two empirical applications in such a way that the tests find a cointegrating rank smaller than one suggested by procedures which accommodate the shifts.
urn:nbn:de:kobv:11-10049310
Keywords: C32; C15; 330; Systems cointegration tests; Level shifts; Monte Carlo study